The Cuba-U.S. bilateral relationship new pathways and policy choices - Moreno, Erika; Kelly, Michael J. 1968-; Witmer, Richard C. 1966- (Oxford University Press, 2019)
This book brings together experts from across three disciplines--politics, economics, and law--to address the key issues that affect Cuba-U.S. bilateral relations today. The chapters identify the opportunities and challenges presented to both nations in each of their respective disciplines while staking out what the future may hold"--